Rat-specific IgG and IgG4 antibodies associated with inhibition of IgE–allergen complex binding in laboratory animal workers. Issue 9 (18th June 2014) - Jones, M; Jeal, H; Schofield, S; Harris, J M; Shamji, M H; Francis, J N; Durham, S R; Cullinan, P
Abstract : Objectives: The relationship between exposure to rodent allergens and laboratory animal allergy is complex; at highest allergen exposures there is an attenuation of sensitisation and symptoms which are associated with increased levels of rat-specific immunoglobulin (Ig)G and IgG4 antibodies. We set out to examine whether the increased levels of rat-specific IgG and IgG4 antibodies that we have previously observed at high allergen exposure in our cohort of laboratory animal workers play a functional role through blockage of the binding of IgE–allergen complex binding to CD23 receptors on B cells. Methods: Cross-sectional survey of laboratory animal workers (n=776) in six UK pharmaceutical companies were surveyed. IgE–allergen complex binding to B cells was measured in 703 (97.9%) eligible employees; their exposure was categorised by either job group or number of rats handled daily. Results: We observed a significant decrease in IgE–allergen complex binding to B cells with increasing quartiles of both rat-specific IgG and IgG4 antibodies (p<0.001). IgE–allergen complex binding to B cells was lower in workers with high allergen exposure, and significantly so (p=0.033) in the subgroup with highest exposures but no work-related chest symptoms. Conclusions: These findings demonstrate a functional role for rat-specific IgG/G4 antibodies in laboratory animal workers, similar to that observed in patients treated with high dose immunotherapy who become clinically tolerant, suggesting a potential explanation for the attenuation of risk at highest allergen exposures.